University students' experiences of sexual harassment: the role of gender and psychological resilience - Athanasiades, Christina; Stamovlasis, Dimitrios; Touloupis, Thanos; Charalambous, Hara (Frontiers in Psychology, 2023)
The present study aimed to investigate university students’ experiences of different types of sexual harassing behaviours, within the academia, as well as the role of gender and psychological resilience regarding their victimisation and its consequences. Overall, 2.134 students (70.5% women), both undergraduates (81%) and postgraduates (19%), completed a self-reported online questionnaire regarding the variables involved (sexual harassment, consequences, resilience). According to the results, the most prevailing types of sexual harassing behaviours, which were experienced mainly by women students, included offensive sexual comments/jokes/stories, inappropriate comments about one's body/appearance/sex life, as well as obscene ways of staring, obscene gestures and/or exposure of body parts causing embarrassment. Accordingly, the perceived psycho-emotional and academic consequences of sexual harassment were more pronounced in the case of women. Furthermore, psychological resilience was negatively associated with gender, making women with low resilience more vulnerable to experiences of sexual harassment and more affected by its consequences. The study highlights important aspects of this gender-based aggressive behaviour in academia and emphasizes the necessity for the implementation of appropriate policies and interventions in higher education institutions against sexual harassment.